SCHOOL LEARNING ACTION CELL AS A REMEDY TO OUT-OF-FIELD TEACHING: A CASE IN ONE RURAL SCHOOL IN SOUTHERN PHILIPPINES - Bajar, Jayson Troy Ferro; Bajar, Mary Ann Ferro; Alarcon, Elizabeth P (International Journal of Educational Management and Innovation, 2021)
Teaching continues to be a persisting problem in the Philippine educational system, which is also evident in the rural school where this study has been conducted. As a remedy, the researchers organized a professional learning community in the form of a school learning action cell (SLAC) to provide capacity-building assistance to out-of-field teachers and promote collaborative working culture. This study aims to determine the intervention's perceived effects by conducting a qualitative inquiry that utilizes grounded theory and thematic analysis. Seven teachers participated and were interviewed post-intervention. Results of the study revealed that SLAC sessions contribute to the general well-being of the teachers in their view of the profession as it 'reduced their tasks’ and 'promoted workplace collaboration.' On the other hand, it also impacted their pedagogy, which was found to have contributed to their 'instructional mastery’ and ‘teacher efficacy.' However, the researchers caution that, though the intervention has been successful, it should be taken in its suggestive nature when out-of-field teaching is unavoidable. Finally, the researchers conclude that, though the intervention was found to be promising, administrators must, whenever feasible, adhere to the idyllic educational landscape and assign teachers according to their respective specialized fields.